Peran Manajemen Sekolah dalam Penguatan Pendidikan Karakter di Sekolah Dasar - SINDY SATAROH; AHMAD RIDWAN (CV. ITTC INDONESIA, 2026)
Strengthening character education is a key priority in the implementation of elementary education in Indonesia. Schools have the responsibility to develop students who excel not only academically but also possess character aligned with the values of Pancasila. The successful implementation of character education is significantly influenced by the effectiveness of school management in planning, organizing, implementing, and evaluating educational programs. This study aims to analyze the role of school management in reinforcing character education in elementary schools through a library research approach. Data were collected from various books, scientific journal articles, and relevant policy documents, and analyzed using content analysis techniques. The findings indicate that school management plays a strategic role in establishing a school culture that supports the internalization of character values. This includes formulating school policies, strengthening the principal’s leadership, developing teachers’ competencies, creating a conducive school environment, involving parents, and conducting continuous evaluations of character education programs. Effective school management can enhance the cultivation of religious values, discipline, responsibility, mutual cooperation, integrity, and students’ independence. Therefore, strengthening character education should be an integral part of the school management system to ensure that all members of the school community share a common commitment to fostering students’ character sustainably